The Effect Of Type 2 Diabetes On The Duration Of Recovery Of Covid-19 Patients In Bogor City Regional General Hospital - Shalzaviera Azniatinesa; Asri C. Adisasmita; Marthino Robinson (Lambung Mangkurat University, 2022)
Diabetes (36.5%) is the second most common comorbidity suffered by COVID-19 patients after hypertension (49.8%) in Indonesia. COVID-19 patients with diabetes have a 52.1% higher risk of being hospitalized. This study aims to determine the effect of diabetes on the recovery time of COVID-19 patients since being admitted to the hospital. A retrospective cohort study was conducted on 339 confirmed RT-PCR SARS-CoV-2 patients. The Cox Proportional Hazard regression test was used to analyze the relationship between diabetes and the length of recovery for COVID-19 patients. The survival probability for a COVID-19 patient without diabetes to recover from hospital stay for more than 12 days is 19.3% and 32.6% for diabetic patients. The median survival to recovery in patients without diabetes was 9 days (95% CI 8.56-9.44), whereas in patients with diabetes it was 10 days (95% CI 8.94-11.06). The average length of recovery needed for COVID-19 patients without diabetes was 13.13 days, and 20.38 days for COVID-19 patients with diabetes. Multivariate analysis showed no significant correlation between diabetes and recovery time with p-value = 0.302 (HR 1.216; 95% CI 0.839 – 1.762). COVID-19 patients with diabetes have a longer median recovery time than patients without diabetes. However, there is no significant relationship between diabetes and recovery time.